Perempuan dan perilaku berkelanjutan dalam komunitas online pecinta barang lokal - Krisna Murti; Raden Ayu Wulantari; Nurly Meilinda; Anang Dwi Santoso (Universitas Bunda Mulia, 2022)
Scholars discovered that the majority of studies studying why women engage in sustainable fashion practices focused on environmental incentive, personal drive, or hedonistic motivation. In fact, women may anticipate the social value of fashion to be associated with the concept of self-improvement rather than the dimension of conservatism. This study aims to determine whether women's fashion consumption serves as a signifier of social identity, class, or position, as well as the degree to which the social value of fashion is embedded inside the product itself. The thesis to be demonstrated in this study is that women are agents of sustainable behavior to transmit sustainable habits because women are grassroots agents with the most influence in daily life. This research is based on a constructivist paradigm with a qualitative method that enables researchers to comprehend how behavior from the perspective of research subjects (women) with their subjective understanding underpins the sustainable behavior that they practice. Seven female agents were interviewed via Zoom meetings or WhatsApp video calls to collect the primary data. This study finds that sustainable fashion consumption has a social value. The social value of sustainable fashion consumption is inherent in the purchase or consumption of these products, as well as in the location where these items are purchased. The implication of this study is that a campaign to promote sustainable fashion consumption may incorporate social values.